Credit & Liquidity Risk of Asia Pacific Islamic Bank: Evidence from Indonesia & Malaysia - Resi Asrianti; Yaser Taufik Syamlan (Universitas Airlangga, 2021)
This study aims to analyze the effect of Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Bank Age, Non Performing Financing (NPF), and Return On Assets (ROA) on the level of risk taking of Islamic banks in Indonesia and Malaysia. Risk taking in this study is proxied by Financing Asset Ratio (FAR) and Financing to Deposit Ratio (FDR). The data used in this study are the cross section data of Islamic banks in Indonesia and time series data of 2010 to 2017 from each of the financial statements of Islamic banks in Indonesia and Malaysia which act as the object of this research. This research uses panel data regression method. Based on the analysis, The TPF and the CAR has big impact on the Credit and Liquidity Risk in both observed country. CAR significantly influenced the credit risk, when the CAR goes up, it is resulted from the addition of equity due to the rise of NPF. Moreover, in the liquidity risk in Indonesia is caused by the mismatch nature of Indonesian funding side. On the other hand, the credit risk in Malaysia rises whenever the TPF increase and the liquidity is caused by the deposit taking and risk taking activity. The introduction of investment account by the Bank Negara is among the factors of significant as well as negative result of it. This paper urges the OJK to speed up the implementation of Investment Account product in Indonesian Islamic bank since it will reduce the liquidity risk and at the end will decrease the credit risk.